Trainee doctors' preparedness for clinical work in geriatric psychiatry: a survey on 18 preliminary entrustable professional activities - Lerch, Seraina Petra; Pinilla, Severin; Nendaz, Mathieu; Klöppel, Stefan; Huwendiek, Sören (International journal of geriatric psychiatry, 2023)
Background: Research concerning transitions from one rotation to another during medical specialist training is scarce. This study examined trainee doctors' perceived preparedness for core clinical activities, trainee doctors' preparedness levels, and general perceptions of medical specialist training in geriatric psychiatry. Method: Swiss trainee doctors in geriatric psychiatry were surveyed about their perceived preparedness for 18 preliminary entrustable professional activities (EPAs), curricular support, and general perceptions of their medical specialist training. Closed questions were analysed using descriptive statistics, while open questions were subjected to content analysis. Results: The participants comprised 48 trainee doctors (30.4% response rate) who differed in their educational experience (years of residency and specialism) and clinical subspecialisation goals. Trainee doctors felt adequately prepared for most EPAs but less prepared for some, including electroconvulsive therapy, psychotherapy, and treating older adults in the home environment or residential facilities. Despite the trainee doctors' diversity, they did not differ significantly in perceived preparedness for most EPAs. The most often offered suggestions for improving geriatric psychiatry training were intensified clinical supervision and a structured induction programme. Conclusion: Trainee doctors reported that they felt sufficiently prepared for most EPAs, regardless of their backgrounds and professional goals. However, several professional activities in geriatric psychiatry warrant further training. Our findings indicate the need for a higher intensity of clinical supervision (e.g. more direct observation and specific feedback), the introduction of structured induction programmes (e.g. orientation week), and specific teachings (e.g. on neurocognitive assessment).